Quintessence of Dust: The Science of Matter and the Philosophy of Mind - Harry Redner (Brill, 2020)
Quintessence of Dust by Harry Redner argues for a science of matter and a philosophy of mind based on emergence. Mind emerges from matter through five essential stages – “quintessence” (Hamlet). Human mind is differentiated from animal mind primarily by reference to art (Homo ludens). This approach draws support from Donald, Edelman and other palaeoanthropologists, psychologists and neurologists. The emergent relation between two entities is defined as an indissoluble non-identity. The “mind as machine” thesis, artificial intelligence and cognitivism are criticised. The alternative emergentist approach comes close to Spinoza. The book attempts a synthesis of the natural sciences, social sciences and humanities based on philosophic premises.'... I find the core of the argument, as well as its exposition, coherent, convincing and illuminating... I put Quintessence of Dust in the top 5% of books in the field.'-Miguel Candel Sanmartin, University of Barcelona, in Thesis Eleven August 2022